Unraveling the Relationship among Philosophy, Science and the Quran - Chaerul Mundzir; M. Ilham; Hasim, Hasanuddin; Luthfi, Mochtar (Pappaseng: International Journal of Islamic Literacy and Society, 2025)
This study aims to analyze the relationship among philosophy, science, and the truth of the Qur'an, as well as how understanding of the truth of the Qur'an can interact with modern scientific findings. The method used in this study is a literature study with a qualitative approach, analyzing various sources of literature, including scientific works and contemporary interpretations, as well as comparisons with the latest scientific discoveries. This research highlights the importance of contextual interpretation of the revelation of the Qur'an in understanding the truth contained in it, both from a spiritual and scientific perspective. The results show that there is a harmonious relationship between the truth in the Qur'an and scientific principles, although sometimes there are challenges in integrating textual understanding with scientific discoveries. The Qur'an not only provides truths that are eternal and universal but also open to interpretation that can be adapted to the development of science without compromising the essence of revelation itself. In conclusion, the relationship between philosophy, science, and the truth of the Qur'an shows that the two complement each other, where science can be used to delve into the phenomena described in the Qur'an. The implication of this research is the importance of an interdisciplinary approach that combines religious science and science to understand the truth holistically and relevant to the development of the times.